2010
DOI: 10.1111/j.1745-3933.2010.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

The discovery of a very cool, very nearby brown dwarf in the Galactic plane

Abstract: We report the discovery of a very cool, isolated brown dwarf, UGPS 0722???05, with the United Kingdom Infrared Telescope Deep Sky Survey (UKIDSS) Galactic Plane Survey. The near-infrared spectrum displays deeper H2O and CH4 troughs than the coolest known T dwarfs and an unidentified absorption feature at 1.275 ??m. We provisionally classify the object as a T10 dwarf but note that it may in future come to be regarded as the first example of a new spectral type. The distance is measured by trigonometric parallax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
167
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(180 citation statements)
references
References 27 publications
13
167
0
Order By: Relevance
“…On the other hand, the z-band photometry obtained by Lucas et al (2010) for the T10 dwarf UGPS J0722−0540 leads to M z values between 22.4 and 22.6, about 1 mag fainter than our values.…”
Section: Photometric Classification and Distancesmentioning
confidence: 44%
See 1 more Smart Citation
“…On the other hand, the z-band photometry obtained by Lucas et al (2010) for the T10 dwarf UGPS J0722−0540 leads to M z values between 22.4 and 22.6, about 1 mag fainter than our values.…”
Section: Photometric Classification and Distancesmentioning
confidence: 44%
“…A lower resolution spectrum of the T8 template 2MASSI J0415195−093506 (from Burgasser et al 2004) is overplotted. Arrows mark the candidate NH 3 absorption feature, mentioned by Lucas et al (2010).…”
Section: Photometric Classification and Distancesmentioning
confidence: 99%
“…The project summarized here was motivated by the recent discoveries of nearby stellar and sub-stellar objects (e.g., Artigau et al 2010;Lucas et al 2010;Luhman 2013;Mamajek et al 2013;Scholz 2014, among others), the implications that these findings may have on the stellar census in the Solar neighborhood (Henry et al 2006;Faherty et al 2009;Winters et al 2015), new results in the multiplicity of young low-mass stars and brown dwarfs in the field and young moving groups (Delorme et al 2012;Elliott et al 2014), and even the dynamic interactions of the Solar system Mamajek et al 2015). The paper is organized as follows: Section 2 describes the catalogs and methods we used to generate a list of objects of interest, and the instruments we used to follow up and characterize them.…”
Section: Introductionmentioning
confidence: 99%
“…Near-IR spectral standards for earlier types can be found in Kirkpatrick et al (2010) (Warren et al 2007;Delorme et al 2008b;Burningham et al 2008). Lucas et al (2010) reported the discovery of an even cooler object UGPS 0722−05 which they suggested should be classified as T10, and could in the future be regarded as the first example of a new spectral type. In 2011, Cushing et al (2011) reported the 'Discovery of Y-dwarfs'.…”
Section: Y Dwarfsmentioning
confidence: 99%